Biodistribution and toxicity assessment of methoxyphenyl phosphonium carbosilane dendrimers in 2D and 3D cell cultures of human cancer cells and zebrafish embryos - Zuzana Žmudová; Zuzana Šanderová; Michaela Liegertová; Stanislav Vinopal; Regina Herma; Luděk Sušický; Monika Müllerová; Tomáš Strašák; Jan Malý (Scientific Reports, 2023)
Abstract The consideration of human and environmental exposure to dendrimers, including cytotoxicity, acute toxicity, and cell and tissue accumulation, is essential due to their significant potential for various biomedical applications. This study aimed to evaluate the biodistribution and toxicity of a novel methoxyphenyl phosphonium carbosilane dendrimer, a potential mitochondria-targeting vector for cancer therapeutics, in 2D and 3D cancer cell cultures and zebrafish embryos. We assessed its cytotoxicity (via MTT, ATP, and Spheroid growth inhibition assays) and cellular biodistribution. The dendrimer cytotoxicity was higher in cancer cells, likely due to its specific targeting to the mitochondrial compartment. In vivo studies using zebrafish demonstrated dendrimer distribution within the vascular and gastrointestinal systems, indicating a biodistribution profile that may be beneficial for systemic therapeutic delivery strategies. The methoxyphenyl phosphonium carbosilane dendrimer shows promise for applications in cancer cell delivery, but additional studies are required to confirm these findings using alternative labelling methods and more physiologically relevant models. Our results contribute to the growing body of evidence supporting the potential of carbosilane dendrimers as vectors for cancer therapeutics.